The Role Of Education And Environmental Awareness In Promoting Ecopreneurship Among The Younger Generation - Nurul Mardhiah Sitio; Gessan Kurnia Dewi; Tofa Waluyo Alifya; Risco Christianto Ondang (International Forum of Researchers and Lecturers, 2025)
Bandung Regency, which is experiencing overcapacity in landfills, has implemented a waste management solution involving the separation of organic and inorganic waste. Inorganic waste, which is notoriously difficult to decompose, has prompted the Bandung Regency government to adopt a community-focused approach to waste management, establishing waste banks in school-age communities. However, the project has encountered challenges, as evidenced by the fact that some schools have implemented waste banks but have not been actively engaged in their operations. This has led to the project's suboptimal implementation in Bandung Regency schools.The objective of this study is to identify the challenges associated with the inactivity of waste banks in Bandung Regency schools, as perceived by students and administrators.The study utilises the triple drivers of ecopreneurship, focusing on the economic, social, and environmental benefits of school waste banks. This research employs a mixed methods approach, utilising both quantitative and qualitative data collection methods. The quantitative approach involves the administration of surveys to students, followed by data processing using descriptive statistics. The qualitative method involves conducting interviews with administrators, and the data is processed using the Miles and Huberman model. The findings of the research indicate that the implementation of a waste bank for the management of inorganic waste in a school environment is positively received by the school, despite the presence of obstacles related to waste collection sites, socialisation among students, and differences between administrators and students regarding the most significant focus or choice for implementing waste banks in schools.It is anticipated that the research results will contribute to the understanding of inorganic waste management in waste banks that are less active in the school environment. The study thus recommends further research in schools that are routine or active in waste bank implementation activities, with a view to describing overall information about the implementation of school waste banks, especially in schools in Bandung Regency with school waste bank projects.